2009
DOI: 10.1590/s1677-55382009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma: a long-term follow-up of 24 patients undergoing laparoscopic adrenalectomy

Abstract: Purpose:- Materials and Methods:- Results: - Conclusions:-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
13
0
4
Order By: Relevance
“…Finally, our long-term follow-up results showed that patients achieved similar outcomes in terms of survival after either procedure, which was consistent with the long-term results of Castilho et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, our long-term follow-up results showed that patients achieved similar outcomes in terms of survival after either procedure, which was consistent with the long-term results of Castilho et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…In human medicine, early reports were skeptical of the procedure and a concern that greater tumor manipulation would precipitate greater hemodynamic instability during anesthesia was highlighted . These early data have been refuted by many more recent studies . Most of these studies have accepted the null hypothesis that there is no difference in hemodynamic instability in people undergoing laparoscopic adrenalectomy compared to those undergoing open adrenalectomy .…”
Section: Discussionmentioning
confidence: 99%
“…Although hospital duration (4.8 vs 3.6 days; P=0.03) and operative time (183 vs 157 min; P=0.01) were longer for pheochromocytoma lesions, morbidity, conversion rate, and other perioperative outcomes were similar between groups. Contemporary series from Castilho et al [11] and Tatsugmai et al [12] have further confirmed the surgical efficacy of laparoscopic adrenalectomy for pheochromocytoma as well as the long-term successful cure.…”
Section: Pheochromocytomamentioning
confidence: 83%